Public Service Delivery at Local Level: Role of Bhalmansa in Community Access to Municipal Services - Bhattarai, Krishna Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2025)
This article explores the role of Bhalmansa, an indigenous governance institution of the Tharu community, in enhancing community access to municipal services. The primary objective is to examine the intersection between Tharu indigenous governance practices and the contemporary local governance system to understand socio-culturally resonant service delivery. Using a sequential mixed-methods approach, data were collected through a household survey, the Key Informant Interviews (KII) and Kuragraphy (informal discussion). The quantitative findings reveal that two-thirds of those who accessed public services required more than three attempts, relying significantly on informal channels such as friends and family members to navigate the challenge of getting services. The qualitative study findings show that, despite the Bhalmansa system’s enduring role in securing community ownership of local development and public service delivery, its influence has weakened. This decline is primarily due to non-recognition by local governments and rigid bureaucratic procedures that undermine the indigenous governance system. The study’s findings underline the need for local policy reforms that integrate indigenous structures like Bhalmansa into local governance. Such integration can foster co-creation and co-production in service delivery and access to education, transforming inclusive public service delivery from a rhetorical commitment into a genuinely community-driven practice.